Problems of Participation Qualification and Sentencing Proportionality in Unlicensed Mineral Mining Offences - Revaldo Revaldo; Jeanne Darc Noviayanti Manik; Sintong Arion Hutapea (Rechtsvinding, 2026)
Unlicensed tin sand mining activities in East Belitung frequently involve multiple perpetrators with varying roles and degrees of participation. This situation demands the careful application of the participation doctrine (deelneming) to ensure that criminal sentences proportionally reflect each actor's culpability. This study analyzes the accuracy of the deelneming doctrine and the judicial reasoning underlying sentencing in Verdict No. 48/Pid.Sus-LH/2025/PN Tdn and Verdict No. 49/Pid.Sus-LH/2025/PN Tdn. The research employs a normative legal method with a descriptive-analytical character using case, statutory, and conceptual approaches. Findings reveal that prosecutors and judges both applied Article 55 paragraph (1) point 1 of the Criminal Code in conjunction with Article 161 of Law No. 3 of 2020, albeit from different perspectives. The co-perpetrator (medepleger) classification for truck drivers in Verdict No. 48 is inaccurate given the absence of double opzet and meeting of minds. Conversely, the medepleger classification of the tin collector in Verdict No. 49 is correct. Sentencing in both verdicts does not fully reflect the proportional difference in culpability, leaving the legal objectives of justice, utility, and legal certainty insufficiently balanced.